GABAA Receptors in Astrocytes Are Targets for Commonly Used Intravenous and Inhalational General Anesthetic Drugs - Chung, Woosuk; Wang, Dian-Shi; Khodaei, Shahin; Pinguelo, Arsene; Orser, Beverley A. (Frontiers in Aging Neuroscience, 2022)
Background: Perioperative neurocognitive disorders (PNDs) occur commonly in older patients after anesthesia and surgery. Treating astrocytes with general anesthetic drugs stimulates the release of soluble factors that increase the cell-surface expression and function of GABAA receptors in neurons. Such crosstalk may contribute to PNDs; however, the receptor targets in astrocytes for anesthetic drugs have not been identified. GABAA receptors, which are the major targets of general anesthetic drugs in neurons, are also expressed in astrocytes, raising the possibility that these drugs act on GABAA receptors in astrocytes to trigger the release of soluble factors. To date, no study has directly examined the sensitivity of GABAA receptors in astrocytes to general anesthetic drugs that are frequently used in clinical practice. Thus, the goal of this study was to determine whether the function of GABAA receptors in astrocytes was modulated by the intravenous anesthetic etomidate and the inhaled anesthetic sevoflurane. Methods: Whole-cell voltage-clamp recordings were performed in astrocytes in the stratum radiatum of the CA1 region of hippocampal slices isolated from C57BL/6 male mice. Astrocytes were identified by their morphologic and electrophysiologic properties. Focal puff application of GABA (300 µM) was applied with a Picospritzer system to evoke GABA responses. Currents were studied before and during the application of the noncompetitive GABAA receptor antagonist picrotoxin (0.5 mM), or etomidate (100 µM) or sevoflurane (532 µM). Results: GABA consistently evoked inward currents that were inhibited by picrotoxin. Etomidate increased the amplitude of the peak current by 35.0 ± 24.4% and prolonged the decay time by 27.2 ± 24.3% (n = 7, P < 0.05). Sevoflurane prolonged current decay by 28.3 ± 23.1% (n = 7, P < 0.05) but did not alter the peak amplitude. Etomidate and sevoflurane increased charge transfer (area) by 71.2 ± 45.9% and 51.8 ± 48.9% (n = 7, P < 0.05), respectively. Conclusion: The function of astrocytic GABAA receptors in the hippocampus was increased by etomidate and sevoflurane. Future studies will determine whether these general anesthetic drugs act on astrocytic GABAA receptors to stimulate the release of soluble factors that may contribute to PNDs.